Analysis of the Influence of Residential Electrical Installation Errors on Prepaid Kwh Meter Errors in the PT PLN (Persero) ULP Stabat Area - Harfan Diansyah; Parlin Siagian; Muhammad Erpandi Dalimunthe (Journal of Engineering, Electrical and Informatics, 2025)
There are several things that happen when customers use electricity with prepaid Kwh meters. One of the problems now is an error in the Kwh meter or commonly called Kwh tempering. This study uses an observation method by taking a sample of 2 houses that have tempering problems in their Kwh. The results of the study of the first house with 900 VA electricity power found a current leak of 0.3 A, and in the second house with 1300 VA electricity power found a grounding cable connected to the neutral cable which caused a limping load of 0.85 A.